Using disney’s theme song to improve the students’ listening skill at eleventh grade of SMAN 13 Bone - Andi Ahmad Mubarak; Nirwana Darwis; Rahmah Wahdaniati Suaib (International Journal of Research on English Teaching and Applied Linguistics, 2021)
The main concern of this research was aimed at improving the listening skill of the grade XI students of SMAN 13 Bone in the academic year of 2020/2021. The researcher used WhatsApp group as a media to communicate with students, face to face cannot be implemented because of the Covid-19 pandemic.  The technique of analyzing data was applied by using quantitative data. The quantitative data was taken from the test. The result shows there was a positive effect of students’ listening skill using Disney’s theme song. It showed from the mean of the Pre-test was 66,43  and the mean score of post-test was 78,0357. From the data, it indicated that using Disney’s theme song in Listening skill was effective. The advantages of using song are: Song could become a media introduction of new languages, songs improve students’ pronunciation, song could be give good contribution in increasing students’ motivation in Listening, and song can strengthen memory of students.